Transcriptomics of diapause in an isogenic self-fertilizing vertebrate. (December 2015) - Mesak, Felix; Tatarenkov, Andrey; Avise, John
Abstract Background Many vertebrate species have the ability to undergo weeks or even months of diapause (a temporary arrest of development during early ontogeny). Identification of diapause genes has been challenging due in part to the genetic heterogeneity of most vertebrate animals. Results Here we take the advantage of the mangrove rivulus fish (Kryptolebias marmoratus or Kmar)—the only vertebrate that is extremely inbred due to consistent self-fertilization—to generate isogenic lineages for transcriptomic dissection. Because the Kmar genome is not publicly available, we builtde novo genomic (642 Mb) and transcriptomic assemblies to serve as references for global genetic profiling of diapause in Kmar, via RNA-Seq. Transcripts unique to diapause in Kmar proved to constitute only a miniscule fraction (0.1 %) of the total pool of transcribed products. Most genes displayed lower expression in diapause than in post-diapause. However, some genes (notablydusp27, klhl38 andsqstm1 ) were significantly up-regulated during diapause, whereas others (col9a1, dspp andfmnl1 ) were substantially down-regulated, compared to both pre-diapause and post-diapause. Conclusion Kmar offers a strong model for understanding patterns of gene expression during diapause. Our study highlights the importance of using a combination of genome and transcriptome assemblies as references for NGS-based RNA-Seq analyses. As for all identified diapause genes, in future studies it will be critical to link various levels of RNA expression with the functional roles of the coded products.